Curriculum Platform Needs: Assessment for AICCRA Partners - Curtis, Ashley (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This report summarizes findings on needs and gaps for a key activity of the AICCRA project-development of a curriculum platform. The AICCRA curriculum platform will be a resource that enables institutions to establish and continually develop curricula that support key competencies/skills in climate services/CSA prioritized by stakeholders in regions.